The chiral proteomic analysis applied to aging collagens by LC-MS: Amino acid racemization, post-translational modifications, and sequence degradations during the aging process - Morvan, Marine; Mikšík, Ivan (Elsevier Science BV, 2023)
Collagen is the most abundant protein in the animal and human bodies, and it is not exempt from this aging phenomenon. Some age-related changes may appear on collagen sequences, such as increased surface hydro-phobicity, the appearance of post-translational modifications, and amino acids racemization. This study has shown that the protein hydrolysis under deuterium conditions is privileged to limit the natural racemization during the hydrolysis. Indeed, under the deuterium condition, the homochirality of recent collagens is preserved whose amino acids are found in their L-form. However, in aging collagen, a natural amino acid racemization was observed. These results confirmed that the % D-amino acids are progressive according to age. The collagen sequence is degraded over time, and a fifth of the sequence information is lost during aging. Post-translational modifications (PTMs) in aging collagens can be a hypothesis to explain the modification of the hydrophobicity of the protein with the decrease of hydrophilic groups and the increase of hydrophobic groups. Finally, the exact positions of D-amino acids and PTMs have been correlated and elucidated.
Chirální proteomická analýza aplikovaná na stárnoucí kolageny pomocí LC-MS: Racemizace aminokyselin, posttranslační modifikace a sekvenční degradace během procesu stárnutí
Keywords: Aging; Chiral separation; Collagen; D -amino acids; Liquid chromatography; Mass spectrometry; Stárnutí; Chirální separace; Kolagen; D-aminokyseliny; Kapalinová chromatografie; Hmotnostní spektrometrie